RELATIONSHIPS WITH EATING EVENTS IN HYPERTENSION IN WOMEN MENOPAUSE POSBINDU "M" SUKARAME KECAMATAN VILLAGE DISTRICT TASIKMALAYA - Eneng Daryanti; Iis Sopiah Suryani; Meti Sulastri; Nani Purnama Fajriani (Journal of Midwifery, 2019)
Abstract-Objective: In women, blood pressure generally increases after menopause. Those who have menopause have a higher risk of hypertension compared to premenopausal. One of the risk factors that can lead to hypertension is diet. Diet in the form of lots of fatty foods, sodium, and cholesterol. Prevention of hypertension can be done by arranging a balanced diet. The purpose of this study to determine the relationship of diet with the incidence of Hypertension in Women. Method: This research uses a correlation analytic method with a cross-sectional approach. The population in this study are all women with menopause as much as 114 people, with the number of respondents in this study were 114 postmenopausal women using total sampling. Retrieving data using the chi-square formula. Result and discussion: It was found that 60.6% of respondents have no good diet also has hypertension, with 0,559 value ρ (> 0.05), the Ha rejected the conclusion shows no relationship between diet respondents with hypertension in menopausal women. Advice for respondents for blood pressure checked regularly and adjust your diet appropriately so that the amount of food consumed by the recommended dietary allowance figures